2021
DOI: 10.15766/mep_2374-8265.11081
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Arrest and Resuscitation in the Prone Patient: An Adult Simulation Case for Internal Medicine Residents

Abstract: Introduction Acute respiratory distress syndrome (ARDS) is present in approximately 10% of ICU admissions and is associated with great morbidity and mortality. Prone ventilation has been shown to improve refractory hypoxemia and mortality in patients with ARDS. Methods In this simulation, a 70-year-old male had been transferred to the ICU for ARDS and was undergoing scheduled prone ventilation as part of his care when he experienced a cardiopulmonary arrest secondary to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Our study involved three weeks of training with repeat practice and role-play simulation patients in turn. The application of situational simulation training in clinical training can improve trainees' clinical knowledge, nursing skills, and communication skills [8], thereby improving the quality of clinical care and patient safety [9]. Our study showed similar findings with effectiveness in knowledge (Table 1) and skills (Table 2).…”
Section: Discussionsupporting
confidence: 77%
“…Our study involved three weeks of training with repeat practice and role-play simulation patients in turn. The application of situational simulation training in clinical training can improve trainees' clinical knowledge, nursing skills, and communication skills [8], thereby improving the quality of clinical care and patient safety [9]. Our study showed similar findings with effectiveness in knowledge (Table 1) and skills (Table 2).…”
Section: Discussionsupporting
confidence: 77%
“…Our learner-reported improvements are similar to those seen in prior cardiac arrest simulation literature, 26,27 and they add to a growing body of evidence supporting the utility of simulation programs to prepare for COVID-19 cardiac arrest and other rare resuscitation events. [13][14][15][16][17][18][19][20]28 Unlike previous work, however, our talk-through walk-through structure and scripted simulation is far simpler to implement in time-, personnel-, and resourceconstrained settings such as those with current outbreaks due to low vaccination rates. While we cannot directly compare our outcomes to a traditional high-fidelity simulation structure, some of our highest-risk communities are less likely to have a dedicated simulation lab.…”
Section: Discussionmentioning
confidence: 99%
“…Simulation is a well-established and effective means of education for code blue training, 13 particularly in preparing for situational variations with which health care teams may have less experience. [14][15][16][17] At the start of the COVID-19 pandemic, several groups successfully used high-fidelity simulation to train staff for airborne isolation code blue. [18][19][20] Unfortunately, this method of simulation requires significant resources, including personnel, time, and expensive equipment, that are limited in many institutions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a study of conventional CPR and prone CPR in six dying patients found that prone CPR was effective in increasing systolic BP even when the patients experienced vasodilatation and severe hypovolemia. It has also been shown that prone CPR was performed on 22 patients undergoing posterior spinal surgery, and 10 patients were successfully resuscitated [15] . Prone CPR uniformly elevates the patient's intrathoracic pressure, thereby restoring their body circulation.…”
Section: Application Of Prone Cardiopulmonary Resuscitation In Poster...mentioning
confidence: 99%